Prevalence of Asymptomatic Malaria in Urban and Semi-Urban Areas in 2016 and 2019, to Gabon - Mbang Nguema , O. A.; Mawili-Mboumba , D. P.; Masiulis, E.; Effame Eya, E.; Batchy Ognagosso, B. F.; Pongui Ngondza, B.; Koumba Lengongo, J. V.; Ndong Ngomo, J. M.; M’Bondoukwe, N. P.; Obiang Ndong , G. P.; Bouyou-Akotet , M. K. (European Journal of Applied Sciences, 2022)
Malaria remains a major cause of mortality and morbidity in sub saharian Africa. Asymptomatic carriers of the parasite contribute to the parasite reservoir and allow the maintenance of malaria transmission. The aim of this study was to assess the evolution of the prevalence of asymptomatic malaria in 2016 and 2019 in Libreville and surrounding areas in Gabon. Thick- and thin-blood smears for malaria diagnosis were performed inpeople, showing no signs suggestive of malaria and having completed a questionnaire during the prospective, cross-sectional studies carried out in July 2016 and April 2019 in urban (Libreville) and semi-urban (Owendo ) in Gabon. A total of 724 participants were included over the two study years; 337 in 2016 and 384 in 2019. The prevalence of asymptomatic malaria was less frequent in 2019: 5.9% vs 12.8% in 2016 (p<0.01). Asymptomatic carriage was more frequent in men regardless of the study period In 2016, under 5 years old, was the most infected population compared to other age groups and in 2018, it was higher among individuals aged 5-15 years old of 7.4%. These populations may contribute to the reservoirs for Plasmodium and thus may strongly contribute to the anchoring of malaria in favorable eco-epidemiological zones. These data highlight the need use of molecular tools to detect submicroscopic infections in asymptomatic individuals.